PENGARUH PENGHINDARAN PAJAK DAN GOOD CORPORATE GOVERNANCE TERHADAP COST OF DEBT - Fatimatuz Zahro; Afifudin Afifudin; Muhammad Cholid Mawardi (Universitas Islam Malang, 2018)
AbstractThis study aims to prove empirically about the effect of Tax Avoidanceand Good Corporate Governance to the Cost of Debt. The population of this studyare all manufacturing companies listed on the Indonesia Stock Exchange, thesampling technique using purposive sampling method. Based on thepredetermined criteria, obtained a sample of 17 companies with a 3-yearobservation period. The method of analysis used in this study is multiple linearregression analysis. The data used in this research is secondary data. The resultsshowed that tax avoidance, proxy of independent board of commissioners, andaudit committee did not affect cost of debt, while the board of directors negativelyaffected the cost of debt. Simultaneously tax avoidance, independent board ofcommissioners, directors, and audit committee have no effect on cost of debt.Keywords: Tax Avoidance, Independent Board of Commissioners, Board ofDirectors, Audit Committee, and Cost of Debt.